Absorption of sugars in relation to intestinal pH (Revista Española de Fisiología, 1950)
In a previous paper the authors had shown that absorption of glucose is not altered by addition of phosphates at pH 7, in spite of the general belief that glucose absorption may be increased by different buffers at the mentioned pH. In the present paper the capacite of the intestine to keep the neutrality of glucose Solutions has been investigated and the pH influence on the absorption of sugars has been revised.Sois’ and Ponz’ method was utilized in rats, three or four succesive experiments of absorption being practiced in the same jejunal loop of each animal (30 minutes for d-glucose and 45 minutes for d-xilose). (lineóse was dissolved at 5.4 per cent and d-xilose at 4.5 per cent, both in different buffer Solutions. Citric acid-phosphate (Mcllvaine, pH between 2.2 and B.0), phosphates (Sorensen, pH bet ween 5.5 and H.0), boric acid-sodium biborate (Palistzsch, pll between 7.0 and 9.0) and carbonate- bicarbonato (pll 10.0) buffers were em- ployed. pH was tested bv electrometric and colorimetric inethods.The jejunum showed great capacity of neutralizing the buiiei Solutions in the loop, neiitralization being slower as the acid or alkaline degree of Solutions was greater. pll changed froin 2.4to i in 60 minutes and from 10.0 to 7.9 in 40 minutes. Neutialization curves of Solutions at pH 2.4, 4.2, 5.6, R.l and 10.0 reinainmg for an hour in the intestinal loop were obtamed. No variation was pioducea in buffer Solutions at pll 7 imd glucose Solutions were also maintained at pH 7 during 60 minutes, thus showing that the buffer action of intystine is sufficient to maintain this pH, addition of buffer Solutions not being necessary. As a consequence the supposed increase of glucose absorption by phosphates could not be explained as a effect of its buffer action.Absorption experiments of d-glucose dissolved in buffers at different pll, showed a notable influence of the pH : in the limits of pl 1 2.3 and luíˆ.O there was an optimum of glueose absorption between 6.5 and 7.5, diminishing progressively towards the acid or alkaline side. A curve of glueose absorption as per pH was obtained. At pH 3.5 and pl I 9.0 the absorption was only 50 per cent of the optimum.Contrary to what has been asserted, d-xilose absorption also de pended on pll but not so much as that of d-glucose. It must be pointed out that d-xilose absorption is to a certain degree selective.